Corneometric features in atopic dermatitis under the conditions of filaggrin dysmorphism in children - Reshetylo, O. V. (Journal of Education, Health and Sport, 2018)
The objective: to study the morpho-functional state of the skin in atopic dermatitis in children, taking into account the polymorphism of filaggrin protein genes. Materials and methods. 111 children with atopic dermatitis (AD) aged 3 - 11 years old were examined. In addition to general-clinical and allergic examination, a molecular-genetic analysis was conducted to detect polymorphism in the filaggrin gene (FLG). The hydration of the skin was measured by corneometry. Statistical processing of the material was performed using Statistica software 6. Results. It has been established that in 51 AD children (45.9% ± 6.98) polymorphism of FLG took place. Mutation of R501X occurred in 40 children (78.4 ± 5.76%), polymorphism of 2282del4 had 4 patients (7.8 ± 3.76%), combined variant of R501X and 2282del4 took place in 7 (13.7 ± 4.81%) patients. The influence of FLG structural changes on the morpho-functional state of the skin was revealed. It was reflected by a significant decrease in the moisture content of the epidermis (p <0.05). In all main group patients the mean corneomy index was less than 45 points and in 17 children (33.3 ± 6.6%) ≤ 30 points, which corresponds to the status of "very dry skin"; in the control group only 18 children (30% ± 5.9) had skin moisture content less than 45 points; there were none patients with corneometry indices ≤30 points in the control group. The clinical course of AD in the presence of FLG polymorphism is characterized by an early debut (up to 3 months; p <0.001) and more severe course of the disease ( p <0.001); predominaning sensitization to fungal and domestic allergens ( p <0.05). Conclusions. Polymorphism in FLG in AD children was found in 45.9% of the patients under examination. R 501X mutation was found in 78.4% of children, 2282del4 polymorphism in 7.8% of patients, its combined version (R501X and 2282del4) took place in 13.7% of patients. FLG polymorphism leads to a significant reduction in the skin’s moisture in AD children, triggers its early debut and more severe course, promotes sensitization to domestic and fungal allergens.